Literature study: Factor analysis of dominant physical conditions in petanque sports - Haq, Aisyah; Jariono, Gatot; Subekti, Nur; Nurhidayat, Nurhidayat (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
The problem faced by coaches so far is that the dominant physical condition factor in the sport of petanque is not known yet, so that coaches have difficulty in planning training programs as well as looking for athlete talent. Based on these problems, considering that petanque is a newly developed sport in Indonesia, this research has an urgency to find out the dominant physical condition factors in petanque. This research is a qualitative analysis using the literature review method or literature study. The method of collecting data samples in this study was carried out by searching for relevant journals or articles in the research journal database and searching via the internet. The databases used include: Google Scholar and Researchgate. Articles or journals that match the review criteria and have a correlation with the analysis of physical condition factors in petanque sports, then reviewed and analyzed the content contained in the research objectives and outcomes or research findings. From the results of the article search, 9 articles were identified that had related and interconnected topics. After thorough analysis, it was found that the most dominant physical conditions in the sport of petanque that were most often reviewed, and the most dominant in the total of all articles included arm muscle strength, wrist flexibility, balance, and eye-hand coordination